Do domestic and foreign fund managers have similar preferences for stock characteristics? A cross-country analysis - Covrig, Vicentiu; Lau, Sie Ting; Ng, Lilian (Journal of International Business Studies, 2006)
Using a new unique data set on mutual fund stockholdings, we identify several interesting similarities and differences in the stock preferences of domestic and foreign fund managers from 11 developed countries. Results show that both groups of managers prefer stocks with high return on equity, large turnover, and low return variability, and that they also exhibit differential investment behavior. Domestic managers also favor firms that pay large dividends, have low financial distress and high growth potential, whereas foreign managers prefer to invest in corporations that are globally well known. The demand for globally visible stocks by foreign managers is especially strong when their fund mandate is to diversify globally or across regions, and is weakened when their stock holdings are concentrated mainly in a specific local market. The results also show no difference in the stock preferences of American-, European- and Asian-based funds. In general, our overall evidence suggests that the differential mandates of fund managers and hence the geographic allocations of their fund investments influence their stock preferences, but not the geographic location of the managers.